Impact of donor and recipient CYP3A5 and ABCB1 genetic polymorphisms on tacrolimus dosage requirements and rejection in Caucasian Spanish liver transplant patients. (11th September 2013) - Gómez‐Bravo, Miguel Angel; Salcedo, Magdalena; Fondevila, Constantino; Suarez, Francisco; Castellote, José; Rufian, Sebastián; Pons, José Antonio; Alamo, José María; Millán, Olga; Brunet, Mercè
Abstract Studies of liver transplant (LT) patients, mainly in Asians, have evaluated the influence of the CYP3A5*1 allele and P‐glycoprotein gene ABCB1 on tacrolimus pharmacokinetics or biopsy‐proven acute rejection (BPAR) incidence, with no conclusive results. To investigate these issues, 98 Caucasian Spanish LT patients with tacrolimus, mycophenolate mofetil and steroids and 88 cadaveric donors were genotyped for the SNPs CYP3A5 6986G>A, ABCB1 1236C>T, ABCB1 2677G>A/T and ABCB1 3435C>T;. On day 7 post‐LT, patients with a native CYP3A5*1 allele had significantly lower tacrolimus trough concentrations C0 (P = .03) and dose‐adjusted concentrations C0/D (P = .02) than CYP3A5 *3/*3 homozygotes. Three months post‐LT, patients carrying a liver with CYP3A5*1 had significantly lower C0/D (P = .03) and took significantly higher tacrolimus doses (P = .03) than the corresponding *3/*3 homozygotes. ABCB1 SNPs showed no significant association with tacrolimus variables. The 3‐month incidence of BPAR was 10.2%, with no statistically significant differences related to CYP3A5 (14.3% in expresser vs. 9.5% in non‐expresser) or ABCB1 genotype of either patient or donor. We conclude that in Caucasian Spanish LT patients, a native or graft‐borne CYP3A5*1 allele tends to lower tacrolimus concentrations and increase dosage needs, but has no significant impact on the incidence of BPAR.